Didactic and teaching planning from the teacher's viewpoint - Souza, Maria Clara de Lima; Costa, Ademárcia Lopes de Oliveira (The ESPecialist, 2024)
Didactics is of paramount importance in professional teacher training, since it encompasses the didactic elements that result in the teaching and learning processes. In this way, the good elaboration of the planning, element that is part of the didactics, is fundamental for the educational practice because it is through this document that the teacher approaches what will be carried out in the classroom, being necessary, to choose the objectives, contents, methodologies , resources, and reviews. In this context, the present study is inserted, whose objective is to analyze the conceptions of a professor on the subjects didactics, planning and evaluation. This is a qualitative, descriptive research, with the use of bibliographic review and field research, through a questionnaire, carried out with a teacher who works in Elementary and High School, in the area of Biological Sciences. The results show that the participant knows the concepts of Didactics and its tools, but the structural difficulties in the school hinder the good development of the educational practice. Therefore, in view of the answers obtained in the questionnaire, it is clear that the process of his work is always focused on the student to meet the needs of the reality he lives, from the preparation of planning with the choice of contents and methods to the practice of teaching in order to to develop a cognitive, critical, realistic and reflective being about the world around him.